The Meaning of Environmental Journalism for Comic Journalists in "Stories from the Sea" on Social Media Instagram @JurnalisKomik - Dewi, Eriyanti Nurmala; Darmawan, Ziddan Dwi; Sadiyyah, Zulfanida Nurul; Sugiarta, Nugraha (Sinergi International Journal of Communication Sciences, 2024)
This study explores the experiences, motives, and meanings of environmental journalism for comic journalists in Stories  from The Sea on the Instagram account @JurnalisKomik. Using a qualitative method with Alfred Schutz's phenomenological approach, this research examines how comic journalists perceive and convey environmental issues through visual storytelling. The findings reveal that environmental journalism is a field that presents environmental news with a meticulous and detailed reporting style, allowing the emergence of activism in journalism. Furthermore, environmental journalism should be considered a public issue, as many aspects of environmental sustainability are closely related to society. Therefore, there is a need for exemplary environmental journalists whose work can inspire various media, communities, and institutions. Their role is crucial in raising public awareness about environmental issues and encouraging collective action for environmental preservation.